Estudo exploratório dos fatores determinantes de fraude corporativa em empresas brasileiras de capital aberto - Manvailer, Ramão Humberto Martins (Universidade do Vale do Rio dos Sinos, 2021)
This research aims to analyze determinants of corporate fraud in 331 Brazilian open capital companies in activities, available in Brasil, Bolsa, Balcão (B3), for the full period of 2010-2018. Results from this study are supported by The Agency, The Economic crime and The Finance Theories, from which five hypothesis were elaborated. In addition, at the end, the general hypothesis of Cressey (1953) was evaluated. Such hypotheses test probability, considering as Proxy to the fraud of administrative process which were ratified by Securities Commission (CMV). Hypothesis H1 was confirmed and hypotheses H2, H3, H4 and H5 were rejected. The hypothesis H1 tested whether the probability of fraud is negatively affected by the economic-financial performance of the company; the hypothesis H2 tested if the probability is positively affected by company profit sharing; regarding to the hypothesis H3, whether it is negatively affected by composition of Fiscal Council and independence of Administrative Council; the hypothesis H4, in turns, made it possible to find out whether the probability is negatively affected by ownership concentration; the hypothesis H5 tested if the probability is negatively affected by Chief Executive Officers (CEO) with higher level of education; and the hypothesis H6, in the end, checked if the three dimensions of The Fraud Triangle - Pressure, Opportunity and Rationalization -, together, indicate the probability of occurrence of corporate fraud. The observed results indicate that the return on assets (ln_roa), the average remuneration (ln_rem) and the element cash hold (cash_hold) presented statistical significance and the three coefficients showed negative sign, thus indicating an opposite relationship with the variable fraud (PAS). The three coefficients suggest the Pressure over financial return, over available cash and, as opposed to the expected, over average remuneration confirms the H6. Based on that, it was concluded that these coefficients are determinant of fraud occurrence in companies. In being the variables return of assets (ln_roa) and average remuneration (ln_rem) part of the dimension Pressure, it is understood that dimension might be considered regarding to the risk of corporate fraud. The results also pointed out to the dimension Rationalization, through the variable undergraduate educational training. However, The general hypothesis of Cressey was not possible to confirm with the three dimensions. Even so, this achievement may be considered as an excellent finding in this investigation. The verification of the dimension Pressure of Cressey´s Fraud Triangle (1953) indicates that people in positions of trust become agents of trust violation when they come across unshared financial problems, and they suppose these problems may be solved secretly, thus causing the breach of the trust which have been attributed to them. Similarly, the finding about statistic significance with negative sing regarding to the variable cash hold (cash_hold), in every models and also in the totally of hypotheses is a valuable contribution, thus corroborating with the dimension Pressure of the general hypothesis of Cressey (1953). Such analysis denotes that financial pressure are determinants in the action of corporate frauds.
Keywords: Fraudes corporativas; Processos administrativos sancionadores; Governança corporativa; Triângulo de fraudes de Cressey; Corporate fraud; Sanctioning administrative processes; Corporate governance; Cressey’s fraud triangle; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis